2019
DOI: 10.1055/s-0039-1693048
|View full text |Cite
|
Sign up to set email alerts
|

Midcarpal Structure Effect on Force Distribution through the Radiocarpal Joint

Abstract: Background Wrist structure is complicated by distinct anatomical patterns. Previous studies defined radiographic wrist types based on lunate and capitate shape within the midcarpal joint. We hypothesized that these disparate structural patterns will transfer forces differently through the wrist. Objective This study aims to correlate force transferred to the distal radius and ulna with morphological measurements in cadaver arms. Methods Radiographs from 46 wrists, previously tested for forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Most studies have suggested that there is a more stable midcarpal joint in type 2 wrists and that a type 2 joint transfers forces more radially toward the scaphoid and scapholunate ligament than a type 1 wrist. 3,14,15 This study found that type 2 wrists experience increased force transfer (as inferred by motion that is predicted by the model) both in the coronal (medial-to-lateral) and axial (proximal-to-distal) planes. Since this will transfer forces in the direction of the scapholunate ligament, it is likely that there is more load on the scapholunate ligament in a type 2 wrist while performing certain tasks.…”
Section: Discussionmentioning
confidence: 55%
“…Most studies have suggested that there is a more stable midcarpal joint in type 2 wrists and that a type 2 joint transfers forces more radially toward the scaphoid and scapholunate ligament than a type 1 wrist. 3,14,15 This study found that type 2 wrists experience increased force transfer (as inferred by motion that is predicted by the model) both in the coronal (medial-to-lateral) and axial (proximal-to-distal) planes. Since this will transfer forces in the direction of the scapholunate ligament, it is likely that there is more load on the scapholunate ligament in a type 2 wrist while performing certain tasks.…”
Section: Discussionmentioning
confidence: 55%
“…In a cadaver study, Wollstein et al found similarly that a type 1 wrist transferred more force ulnarly in the radiocarpal joint than a type 2 wrist. 6 This finding is counterintuitive in that we expect the type 2 midcarpal joint to be more stable due to the lunate hamate articulation and therefore to transfer forces more ulnarly, i.e., less toward the scapholunate joint. A kinetic in vivo study by Abe et al found more triquetral motion and lunate-triquetrum motion with increased shearing forces to the lunotriquetral interosseous ligament, as well as increased hamate lunate shear in type 2 lunates.…”
Section: Discussionmentioning
confidence: 94%
“…4,5 This variation has been shown to affect load transfer in between the ulna and radius. 6 Assuming that these structural disparities will affect load transfer through the midcarpal joint, the purpose of this study was to:…”
Section: Introductionmentioning
confidence: 99%
“…A cadaver study examining the difference in distribution of forces to the radiocarpal joint demonstrated that a wrist type 2 transfers forces radially to the SL joint and radius while a wrist type 1 transfers the forces differentially in a more ulnar direction. 19 This differential transfer radially in type 2 wrists can explain failure of the SL ligament with repeated trauma or significant one-time injury and the development of the typical SLAC pattern with initial wear at the radial styloid-scaphoid joint followed by involvement of the whole radial-scaphoid joint. This disparate transfer of forces may also explain why in a type 1 wrist the radial-scaphoid joint remains relatively spared and the wrist tends to develop wear in just the midcarpal joint.…”
Section: Discussionmentioning
confidence: 96%